W-RSAUnet: Wavelet Integrated Residual Spatial Attention with Adaptive Spectral Patching for Distal Airway Extraction - P. Sutha,Dr. R. Shenbagavalli (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Automated 3D pulmonary airway segmentation remains a formidable challenge due tothe exponential thinning of distal branches and the extreme sparsity of bronchial structureswithin high-resolution CT volumes. Standard deep learning architectures are plagued with feature erosion during downsampling, resulting in fractured tree topologies. In this work, we propose W-RSAUnet, a dual-domain learning framework